ANALISIS KINERJA ALGORITMA ADVANCED ENCRYPTION STANDARD (AES) TERMODIFIKASI DALAM ENRKIPSI DAN DEKRIPSI DATA - Candra Aditya Pinuyut; Ema Utami; Alva Hendi Muhammad (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
Advanced Encryption Standard (AES) is one of the most popular algorithms used. This research aims to analyze the performance of the Advanced Encryption Standard (AES) algorithm which has been modified in the encryption and decryption process. The main focus of this research is to measure the value of the Avalanche Effect, throughput, and speed of the encryption and decryption process of modified AES by replacing the mixcolumn function with permutation bits and reducing the rotation of conventional AES algorithms, twofish, serpent, DES and 3DES. The results show that the modified AES algorithm has an Avalanche Effect of 50.20%, higher than the conventional AES algorithm which has an Avalanche Effect of 49.63%. Througput testing shows that modified AES does not experience significant changes compared to the standard AES algorithm, Serpent, Twofish, DES and 3DES during the encryption process and experiences significant changes during the decryption process of 467.37% 46 compared to DES and 1286% compared to 3DES.